TQM and performance linkage in the microfinance institutions: The mediating role of IT capability - Homaid, Abdo Ali; Minai, Mohd Sobri; Abdul Rahman, Hamzah (Canadian Center of Science and Education, 2015)
The link between Total Quality Management (TQM) and organizational performance measures has become of great interest to both researchers and practitioners alike during the last decade. However, a thorough literature review has revealed such relationship is not being studied in the micro finance institutions and, furthermore, on the effect on Information Technology (IT) capability of such relationship. This paper is written based on a study done to examine the nature of such relationship that revealed the mediating effect of IT capability in the relationship between TQM and the performance of Micro finance banks in Yemen. The study was conducted in 2014 using a questionnaire survey covering 78 branch managers. Using Smart PLS, the results provide a significant relationship between TQM and micro finance institutional performance and also a significant mediating effect of IT capability on the relationship. The elements representing the variables under study are presented and some practical suggestions and contributions are highlighted in the conclusion.